"A culture of caring": Leading differently in the twin pandemics. Issue 1 (11th April 2022) - McCoy-Wilson, Sonya
The twin pandemics of COVID-19 and systematic racism have ushered in a global reckoning. As much of the data indicates, COVID-19 has disproportionately impacted marginalized Black people and people of color. Simultaneously, police brutality and murders of Black people have escalated. Consequently, the movement for Black lives has moved like a wave of human solidarity across the world. These two global crises have disrupted and deconstructed systems. Although many colleges made decisions to return students and faculty to campuses in the fall of 2020, Urban Technical College (UTC) made the decision to keep operations and classes online for the remainder of 2020. The purpose of this paper is to illustrate, through a case study, how a predominantly Black, technical college in Atlanta, Georgia, used culturally responsive leadership to guide its campus community.